양측성 원발성 부신 침범의 T-림프모구백혈병/림프종 1예 - 정철민; Chul Min Jung; 송서영; Seo Young Song; 김선욱; Sun Wook Kim; 이동현; Dong Hyun Lee; 정호철; Ho Chul Jung; 이호진; Ho Jin Lee; et al. (The Korean journal of medicine, 2014)
현재까지 성인에서 보고된 부신의 원발 림프종은 B세포에서 기원하는 경우가 드물게 보고되었다. 저자들은 복통을 주소로 내원한 51세 여자 환자에서 양측 부신의 종괴를 확인하였고 이후 DIC가 동반되는 급격한 임상 경과를 보인 T- 림프모구백혈병/림프종을 경험하였기에 문헌고찰과 함께 보고하는 바이다. T-lymphoblastic leukemia/lymphoma is an aggressive condition with frequent involvement of the mediastinum, occurring most frequently in older children, adolescents, and young adults. The involvement of extranodal sites is less common, and abdominal dissemination is unusual, but when present it primarily involves the liver and spleen. However, primary lymphoma of the adrenal glands is rare. The majority of reported cases presented with a B-cell immunophenotype. Herein, we report the case of a patient with T-lymphoblastic leukemia/lymphoma who presented predominantly with bilateral adrenal masses without lymphadenopathy, and whose clinical course deteriorated rapidly. (Korean J Med 2014;86:770-773)